Respiratory phenotype and health care utilization patterns by adults with sickle cell disease - Atu Agawu; Nii Nortey; Charleen Jacobs; Alexis Zebrowski; Michelle P. Lin; Jeffrey Glassberg (Blood Advances, 2025)
Abstract: Adults with sickle cell disease (SCD) and asthma have increased mortality and health care utilization; however, there are individuals with respiratory symptoms (including cough and wheeze) without asthma. These individuals may have similar patterns of increased mortality and health care utilization. To characterize the association between respiratory phenotype and health care utilization by adults with SCD. Cross-sectional study of adults with SCD presenting for emergency and inpatient hospital care from 2012 to 2014 in Florida, Iowa, and New York using state-level health care utilization databases. Outcomes of interest included all-cause, SCD-related acute, painful episode, and acute chest syndrome–related care. Respiratory phenotype was defined as SCD + asthma, SCD + respiratory symptoms, and SCD + none. We built multivariable logistic regression and negative binomial regression models to evaluate the association adjusting for demographics, social determinant of health proxies, year of care, and state. Of 29 952 identified individuals, 3.4% had intermittent respiratory symptoms, and a larger proportion (15.6%) had asthma. There was a high rate of inpatient hospitalizations (43%) and emergency department visits (60%). Individuals with asthma had a higher annual risk of inpatient hospitalizations (48% vs 37%) but lower annual risk of an emergency department visit (62% vs 86%) than individuals with intermittent respiratory symptoms. The pattern of increased health care utilization among individuals with intermittent respiratory symptoms was consistent across each utilization type. In this large cohort of adults with SCD, we identified some with intermittent respiratory symptoms who had significantly increased health care utilization. This warrants further evaluation to understand potential etiologies and interventions.